INCREASING SOIL FERTILITY IN THE DESERT ZONE: A COMPREHENSIVE ANALYSIS - Haydarov Hasanjon Hakimovich; Kushimov Bakhtiyor Alishovich (American Journals, 2023)
This scientific article provides a detailed analysis of methods and techniques for increasing soil fertility in desert zones. The study explores various strategies, including organic amendments, irrigation practices, agroforestry, and biotechnological approaches. Through an extensive review of the literature, coupled with practical research methodologies, this study aims to present evidence-based recommendations for sustainable soil management in arid regions. The findings highlight the potential for enhancing soil fertility and agricultural productivity in desert ecosystems, contributing to global food security and sustainable development.
Keywords: soil fertility, desert zone, organic amendments, irrigation practices, agroforestry, biotechnological approaches, sustainable soil management, arid regions, agricultural productivity, food security